Cost-Effectiveness Analysis of Group vs. Weblog Telecommunication (Web Tel) Nutrition Education Program on Glycemic Indices in Patients With Non-Insulin Dependent Diabetes Mellitus Type 2: A Randomized Controlled Trial - Derakhshandeh-Rishehri, Seyedeh-Masomeh; Keshavarz, Khosro; Ghodsi, Delaram; Pishdad, Gholamreza; Faghih, Shiva (Frontiers in Nutrition, 2022)
This a randomized controlled trial study with a cost-effectiveness analysis that aimed to compare the cost-effectiveness of group nutrition education with that of Web-Tel nutrition education in the glycemic control of patients with non-insulin-dependent type 2 diabetes mellitus (T2DM). The study was conducted on 105 patients with T2DM for 3 months in Quds health centre of Bushehr province, Iran. The participants were classified based on age and disease severity (hemoglobin A1c level); then, they were randomly assigned to one of the three groups: group education, Web-Tel education, and the control group using block randomization method. The clinical (intermediate) outcome was changes in hemoglobin A1c (HbA1c). Patients' perspective was adopted, and a deterministic one-way sensitivity analysis was conducted to identify the effects of uncertainties. The results indicated that the expected effectiveness was 0.46, 0.63, and 0.4; the mean costs was 27,188, 5,335, and 634 purchasing power parity (PPP) dollars for group education, Web-Tel education, and the control group, respectively. The incremental cost-effectiveness ratio (ICER) of Web-Tel education vs. the control group was positive and equal to $21, 613.04 PPP; since it was less than three times of the threshold, the Web-Tel education method was considered as a more cost-effective method than the control group. On the other hand, the ICER of group education vs. control group was $447,067 PPP and above the threshold, so group education was considered as a dominated method compared with the control group. In conclusion, considering the ICER, Web-Tel education is a more cost-effective method than the other two and can be used as the first priority in educating patients with T2DM. The present study was registered in Thailand Clinical Trials Registry (TCTR20210331001).